Upper Pleistocene fauna from the Middle Palaeolithic site of Foz do Enxarrique (Vila Velha de Ródão, Naturtejo Unesco Global Geopark) - Silvério Figueiredo; Luís Raposo; Maria Sousa (Geoconservation Research)
Foz do Enxarrique (FENX) is an open-air archaeological site from the end of the Middle Palaeolithic, with faunal remains and Mousterian industry, dated 44–32 Ka. The faunal accumulation shows evidence of human intervention. It can be seen as a paradigm for the interpretation of taphonomic processes typical of open-air sites and difficulties of interpretation. Foz do Enxarrique preserves a single archeological horizon accumulated in low energy conditions, as shown by the fragmentary bones, the predominance of remains of human-hunted animals and the presence of cut marks on some bones. The Municipality of Vila Velha de Ródão has been aware of the interest in the patrimonial value of this archaeological site. The local authorities implemented and developed a project of museology, becoming one of the few Portuguese open-air Palaeolithic sites with a musealization in situ.